225 Relationship between pole vault biomechanics and previous injuries. (3rd March 2020) - Edouard, Pascal; Sanchez, Hervé; Bourrilhon, Cyprien; Homo, Sébastien; Frère, Julien; Cassirame, Johan
Abstract : Background: During pole vault, a high level of energy is transferred from horizontal speed of athlete to the pole. Several ways of performing the pole vault exist, and could be associated with specific injury risk. Objective: To analyse the potential association between the biomechanical patterns of pole vault and the history of injuries. Design: Retrospective study. Setting: National elite indoor championship and youth national indoor championship (U17 and U20) of pole vault (athletics). Participants: 62 (70.5% of the eligible population participating in the championships) healthy national level male and female pole vaulters. Main outcome measurements: We prospectively collected the pole vault biomechanical data of the run-up and take-off phases of the vault, and we retrospectively collected the history of injuries during the 12 preceding months through an online questionnaire. Results: A total of 62 (70.5% of those participating in the championships) pole vaulters accepted to participated in this study, and benefited from pole vault biomechanical and injury data collection. 77.4% reported having presented at least one injury during the 12 preceding months. Higher mean training duration per week and some parameters of the final run-up (higher speed, higher contact time) and take-off (lower height at impulse) phases of the pole vault were significantly associated with history of all injuries. Conclusions: Although the design of the present study do not allow to determine the cause-consequence relationships regarding the biomechanical patterns and the injury occurrence, this study presents some interesting findings supporting the hypothesis of a relationship between the biomechanics pole vault pattern and the injury risk, which can be helpful in injury prevention perspective.